Common mental disorders during the COVID-19 pandemic in Hong Kong: Age-related differences and implications for dementia risk - Kwok, Jessie O. T.; Yan, Rachel W. K.; Kwok, Charlotte P. C.; Cheng, Gabriel W. H.; Lin, Cuichan; Wong, Brian H. C.; Cheng, Sheung Tak; Lee, Allen T. C.; Lam, Linda C. W. (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has imposed a profound negative impact on the mental health and wellbeing of societies and individuals worldwide. Older adults may be more vulnerable to the mental health effects of the pandemic, either directly from the infection itself or indirectly through the preventive measures. However, the existing literature on mental health in the older age groups has not been consistent so far. The aim of this study was therefore to assess the prevalence of common mental disorders (CMD; including depression and anxiety disorders) given their association with dementia risk, and to further examine age-related differences between older and younger adult’s psychological status during the COVID-19 pandemic. Method: This was a secondary analysis of a cross-sectional survey-study conducted during the second wave of COVID-19 pandemic in Hong Kong. The survey was disseminated through different social media platforms to the general population and included sociodemographic questions, self-reported physical health, and previous encounter with SARS or COVID-19. CMD was the primary outcome and was assessed using the 6-item Kessler Scale. A total of 1030 adults fulfilled inclusion criteria. Results: The prevalence of CMD during the pandemic was 16.1%. Compared to younger adults, older adults were significantly less likely to have a CMD (unadjusted OR=0.07, 95% CI=0.02-0.30, p<0.001), with 18.1 % of younger adults having CMD compared to 1.6 % in the older cohort. Age differences remained significant after controlling for sociodemographic factors, physical health, and previous encounter with SARS or COVID-19 (adjusted OR=0.12, 95% CI=0.02-0.57, p=0.008). Conclusion: Common mental disorders are highly prevalent during the COVID-19 pandemic in Hong Kong, though older adults appeared to be less affected mentally. Present findings highlight the urgent need to implement measures and strategies to mitigate the mental health problems, with particular attention to the younger cohort. Given their association with higher dementia risk, early detection and treatment of depression and anxiety disorders will be of critical importance in providing some relief to the already pressurized dementia burden in the longer term.